Vibration behavior of a 3D-printed hybrid polymer bearing with outer race defect - Dogan, Burcu Kucukoglu; Dal, Abdurrahim; Agoren, Gorkem; Karacay, Tuncay (Emerald Group Publishing Ltd, 2024)
PurposeIn industry applications, polymer hybrid bearings have become widespread in recent years owing to the lack of lubricant requirements, particularly in areas requiring hygiene. The additive manufacturing method gives significant advantages to have complex machinery parts, and it has become popular in the industry in recent years. However, it has some inherent disadvantages caused by layered deposition/addition of the materials, and the probability of the localized defect is much higher than in the conventional manufacturing methods. This study aims to investigate the effect of the outer race defect on the characteristics of vibration and service lifetime of hybrid polymer ball bearings produced with the stereolithography (SLA) additive manufacturing method.Design/methodology/approachIn this study, polymer bearings' races were produced with the additive manufacturing SLA method, and the outer race defect was analyzed with measured vibrations.FindingsThe results show that the additive manufacturing method suggests a practical solution for producing a polymer hybrid ball bearing. On the other hand, the hybrid three-dimensional-printed bearing, which has an outer race defect, worked for approximately 8 h without any problems under a 1 kg load and a shaft speed of around 1,000 rpm. In addition, when there is a defect in the outer and/or inner race of the ball bearing, the crest factor and kurtosis of the vibration are higher than faultless ball bearing, as expected.Originality/valueThis paper provides valuable information on the lifetime and vibration characteristics of polymer hybrid ball bearing produced by means of additive manufacturing.Peer reviewThe peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-06-2023-0183/
Keywords: Additive manufacturing; Vibration analyze; Bearing defect